Ensino-aprendizagem da linguagem do desenho com foco nos seus fundamentos e na figura humana - Oliveira Júnior, Alex Joacir Pessôa (My University, 2020)
This monograph approaches the teaching of drawing language from the fundamentals of this language and the study of the human figure. It presents the history of drawing, the different educational approaches, theories of drawing development, such as Georges-Henri Luquet's. It exposes fundamentals such as structure, symmetry, perspective, composition and tonal values. Develops particularities of the drawing of the human figure, such as proportions and structuring. Explains learning strategies, such as the use of copies and references. As an objective, this monograph seeks to understand the impact of the fundamentals of drawing language and the study of the human figure on the development of youth drawing between childhood and adolescence. A bibliographical research was carried out seeking to gather conceptions of artists and theorists about the subject. A qualitative longitudinal research was also conducted with children and adolescents, aiming to verify the ideas examined in the bibliographic research. From the analyzes performed in the bibliographic research and the results of the longitudinal study, in this work it is concluded that assimilation of the fundamentals of drawing and concepts of the representation of the human figure are important for language learning, as research participants developed their graphic skills related to drawing language (sic).
Este trabalho aborda o ensino da linguagem do desenho a partir dos fundamentos dessa linguagem e do estudo da figura humana. Apresenta a história do desenho, as diferentes abordagens educacionais, teorias do desenvolvimento do desenho, como a de Georges-Henri Luquet. Expõe fundamentos como estruturação, simetria, perspectiva, composição e valores tonais. Desenvolve particularidades do desenho da figura humana, como proporções e estruturação. Explana estratégias de aprendizagem, como o uso de cópias e de referências. Como objetivo, esta monografia busca compreender o impacto dos fundamentos da linguagem do desenho e do estudo da figura humana no desenvolvimento do desenho de jovens entre a infância e a adolescência. Foi realizado uma pesquisa bibliográfica buscando reunir concepções de artistas e teóricos acerca do tema. Também foi feita uma pesquisa longitudinal qualitativa com crianças e adolescentes, objetivando verificar as ideias examinadas na pesquisa bibliográfica. A partir das análises realizadas na pesquisa bibliográfica e dos resultados do estudo longitudinal, neste trabalho conclui-se que assimilação de fundamentos do desenho e de conceitos da representação da figura humana são importantes para o aprendizado da linguagem, tendo em vista que os participantes da pesquisa desenvolveram suas competências gráficas relacionadas a linguagem do desenho (sic).
Keywords: Desenho da figura humana; Arte - Estudo e ensino; Desenho - Estudo e ensino; Desenho - Técnica